Hearing aid verification: Practices and perceptions of South African audiologists - Jared Moll; Zani Burger; Daneel M.P. Jacobs; Retshepisitswe P. Mothibe; De Wet Swanepoel; Faheema Mahomed-Asmail (South African Journal of Communication Disorders)
Background: Hearing aid verification is required to objectively measure hearing aid outputs by ensuring that the amplified speech spectrum closely approximates the prescription goals.